Long-Term Impact of Parental Post-Traumatic Stress Disorder Symptoms on Mental Health of Their Offspring After the Great East Japan Earthquake - Honda, Yukiko; Fujiwara, Takeo; Yagi, Junko; Homma, Hiroaki; Mashiko, Hirobumi; Nagao, Keizo; Okuyama, Makiko; Ono-Kihara, Masako; Kihara, Masahiro (Frontiers in Psychiatry, 2019)
Longitudinal studies of the long-term psychological impact of the Great East Japan Earthquake (GEJE) on parents and their children have been limited. The current study aimed to monitor parents’ post-traumatic stress disorder (PTSD) symptoms and behavioral problems among their children over time, and to analyze their long-term associations, among the survivors of the GEJE. We used data from the Great East Japan Earthquake Follow-up for Children study, which recruited 4–6-year-old children and those children’s parents immediately after the GEJE in March 2011, with ongoing follow-up. Children’s total, internalizing, and externalizing behavioral problems were assessed using the Child Behavior Checklist (CBCL), and parental PTSD was assessed using the Impact of Event Scale-R (IES-R), in 2012 (baseline) and 2014 (follow-up). Parental PTSD symptoms and children’s behavioral problems declined slightly over time, and both showed a significant correlation between the surveys (r = 0.55–0.77, P < 0.001). The association between parental PTSD symptoms and children’s behavioral problems was investigated using multivariate logistic regression analysis adjusting for baseline children’s behavioral problems and other potential confounders. Cross-sectionally, while no significant association was detected in 2012, all types of children’s behavioral problems exhibited significant positive associations with parental PTSD symptoms in multiple logistic regression analysis (adjusted odds ratio [AOR] = 3.03–5.34) but significant negative associations with the number of siblings (two or more) (AOR = 0.14–0.22) in 2014. Maternal educational attainment level (higher than high school education) also showed a significant negative association with children’s total and externalizing behavioral problems (AOR = 0.30 and 0.13, respectively) in 2014. Longitudinally, parental PTSD symptoms in 2012 showed a significant association with children’s internalizing behavioral problems in 2014 after adjusting for children’s behavioral problems in 2012 and parental PTSD symptoms in 2014 (AOR = 4.62). These results suggest that effect of the GEJE on parental PTSD symptoms and children’s behavioral problems was long-term, lasting for at least 3 years. These possibilities should be carefully considered in mental health support for parents and their offspring in areas affected by the GEJE.